Impact of Diabetes on Outcomes of Laparoscopic Cholecystectomy: A Prospective Study - Gohar Ali; Yousaf Jan; Almas Khattak; Jawad Ali; Muhammad Kashif Dawar; Anees Ahmad; Fazal Ullah (Journal of Gandhara Medical and Dental Sciences)
OBJECTIVES